"Blanco (center), Puíg Elias (left) and Antich (second from the right) con dos señeros cubanas que patrocinan una residencia infantil en Sitges". Series of 2 photos. Copied from CNT collection
"Blanco (center), Puíg Elias (left) and Antich (second from the right) con dos señeros cubanas que patrocinan una residencia infantil en Sitges". Series of 2 photos. Copied from CNT collection.